The clinical case of asymtomatic generalized extrapulmonary tuberculosis - L. T. Nikolayan; A. O. Аyrapetyan; R. S. Petrosyan; N. R. Beglaryan (Туберкулез и болезни лёгких)
The article presents the clinical case of extrapulmonary multi-organ tuberculous lesion with involvement of the spine, urogenital and abdominal systems with no clinical manifestations.